THE MODEL OF MACRO DEBRIS TRANSPORT BEFORE RECLAMATION AND IN EXISTING CONDITION IN JAKARTA BAY - Haifa H. Jasmin; Noir P. Purba; Syawaludin A. Harahap; Widodo S. Pranowo; Mega L. Syamsudin; Ibnu Faizala (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Jakarta Bay as one of an area with the densest population in Indonesia became one of the highest contamination level waters in the world includes pollution of debris. Reclamation activities in Jakarta Bay will change the water conditions, and will also affect the distribution of debris at sea. Therefore, this study conducted is to determine the movement of the marine macro debris before and on the condition of the existing reclamation island in the Bay of Jakarta. The method used is simulated by the hydrodynamic model and particle trajectory models using MIKE software. Data needed for the hydrodynamic model, namely wind, tides, bathymetry, and shoreline, while for the trajectory of the particles using a data type of debris, marine macro debris weight, and debris flux. The analysis was performed for hydrodynamic model simulation results and comparison of particle trajectory models. Hydrodynamics simulations indicate if a reclamation island formation does not change significantly in the offshore area, but a simple change in the surface current pattern of the reclamation area, it also causes a decrease in the flow velocity of ± 0.002 to 0.02 m/s at some point. Macro debris particle trajectory simulation shows if after reclamation, macro debris tends to accumulate in the eastern Jakarta Bay in the rainy season (January), as well as in the western and eastern regions during the dry season (July).